The impact of Diversification on Firms' value during the Financial Crisis 2007-2009: Recent Evidence form United Kingdom. - Nguyen, Quynh Nga (2014)
The economic world witnessed an explosion of corporate diversification during 60s and 70s through the flows of buyout, merger and acquisition activities. However, during later decades such as 80s, and 90s, conglomerates narrowed down their businesses or even are not as attractive as former periods. The impact of diversification on firm’s value has been investigated for many years but has still remained inconclusive. The vast majority of studies conclude that diversification destroys firm’s value while the other argues that firm’s choice to involve in diversification is endogeneity, thus, once the endogeneity is controlled, diversification does not destroy firm’s value and even create premium. In this research, I investigate the effects corporate diversification has on UK firms during the financial crisis 2007-2009 which started from the burst of the U.S housing bubble, then, assets’ prices declination, marginal calls, fire sales and deleveraging create a vast systematic failure for worldwide bank system. It is argues that the current crisis restrict firm’s access to external capital market. Thus, diversification not only helps firm reduce risk but also improves the efficient of internal capital market. My study use a dummy variable as indicate whether firm diversify and two statistical techniques which are: Ordinary Least Squares regression (OLS) and panel data estimation for analyze purpose and find that: (i) using sales multiplier approach, diversification destroys firm’s value; (ii) however when asset multiplier approach is use, diversification creates premium. The robustness check uses a different measure of degree of diversification: Herfindahl index and finds that the effect of diversification on firm’s value is opposite to results obtained when diversification dummy variable is used. The effect of diversification on firm’s sales based excess value is reduced significantly. Furthermore, Heckman’s two-step approach and switching regression are used to control for self-selection bias. The estimation results are consistent with OLS and panel data estimation results. The probit estimates indicate that firms operating in energy industry are those most likely to diversify while utilities firms are less likely to diversify. The impacts the financial crisis on firm’s value are differ across measure of crisis.